Kualitas Sludge Hasil Ikutan Proses Pembuatan Biogas dari Feses Sapi Perah dengan Berbagai Kadar Air - Marlina, Eulis Tanti; Hidayati, Yuli Astuti; Benito AK, Tubagus (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
This research aims to study theÂ influence of water content in the production of biogas from dairy cattleÂ feces to the quality of sludge. The method usedÂ inÂ this studyÂ is the experimental method using a completelyÂ randomized design, withÂ threeÂ treatmentsÂ (P1 =Â substrate waterÂ contentÂ of dairyÂ cowÂ feces 40%, P2 = substrate water content of dairy cowÂ feces 60%, P3 = substrate water content of dairy cow fecesÂ 80%Â ) withÂ sixÂ replications. Variables measured wereÂ levelsÂ of NÂ total, P2O5, K2O. TheÂ results showed that 1) the treatment did not significantly affect total N concentration, but significantly different levels of P2O5 and K2O, 2) substrate water content 60% (P1) and 80% (P2) generate levels of P2O5 and K2O are highest, ie 1.03% and 1.13% (P2) and 0.84% and 1.00% (P3).